The theoretical aspects of lingual illustration of ethno-language cognition in the discourse of language intellectualization - Agibalova, Tetyana Mykolayivna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the peculiarities of verbalization of ethno-language cognition through individualized conceptual picture of the world and with the means of linguo-mental capacity. It expounds the language intellectualization as a process of objectifying of new knowledge/conceptions with language symbols, that are reviewed not as motivated by inductive principle of consequence but through individual interpretation and reinteriorization of initial input reality.